Transcending the boundaries of punishment: On the nature of citizenship deprivation - Tripković, Milena (The British journal of criminology, 2021)
Citizenship deprivation is becoming an increasingly standard response of modern states to criminal and other harmful acts. Current academic attempts to determine the sanction’s legitimacy are, however, frustrated by the inadequate understanding of its nature. Departing from a dominant perspective that considers denationalization as punishment, this article conducts an original study of citizenship policies in 37 European democracies and contrasts them with key principles of punishment. The findings raise serious doubts regarding the penal nature of denationalization: I propose instead that denationalization is better understood as a sui generis sanction, which seeks to relieve the polity of those members who fail to satisfy fundamental citizenship requirements. This position has serious implications for our understanding and justification of modern revocation practices.